Queer podcasting as a medium of visibility in Türkiye’s media ecosystem: a content analysis on episodes - ŞENYÜZ, FATMA BİLGE (My University, 2023)
This study examines the content of queer podcasts’ episodes, which have evolved into an alternative media and visibility tool for queer people, beginning with the COVID-19 pandemic in the Turkish media ecosystem. We analyzed all episodes of the 6 queer podcasts that regularly produce content and have uploaded at least 10 episodes, by using a codebook we created. The results of this study indicate that queer podcasts provide an essential and dynamic platform for queer voices and experiences. They are practical and promising channels for queer representation and communication. Besides, by providing a private and intimate listening experience, these podcasts offer in-depth talks and storytelling, information, and entertainment that can aid in promoting an understanding of queer issues. Our results are encouraging and should be validated by studies on queer podcast experiences from other countries.
Keywords: Sosyal ve Beşeri Bilimler; Social Sciences and Humanities; Sosyal Bilimler (SOC); Social Sciences (SOC); podcasting; queer podcast; queer media; queer visibility; content analysis